Mirror Etching of Single Crystalline C-Face 4H-Silicon Carbide Wafer by Chlorine Trifluoride Gas. (1st January 2017) - Okuyama, Shogo; Kurashima, Keisuke; Habuka, Hitoshi; Takahashi, Yoshinao; Kato, Tomohisa
Abstract : In order to evaluate the potential of a non-plasma dry etcher for silicon carbide, a 50-mm-diameter C-face 4H-silicon carbide wafer was etched using chlorine trifluoride gas at 500°C. The wafer deformation was sufficiently small after the repetitive etching, even though the wafer was very thin, that is, about 160-μm thick. When the wafer surface was significantly etched, concentric-circle-shaped valleys were formed at the radii corresponding to the circular-shaped arrays of pinholes at the gas distributor. Because the local pattern of the 4H-silicon carbide wafer etching rate corresponded to that of the chlorine trifluoride gas supply, the etching rate distribution was determined to be mainly governed by the chlorine trifluoride gas flow. Because the surface morphology and roughness after the etching was comparable to that of the mirror-polished wafer surface, the etcher evaluated in this study was expected to have a significant potential for mirror etching.